Bioarchaeological studies of life in the age of agriculture : a view from the Southeast - Lambert, Patricia M., 1958- (University of Alabama Press, 2000)
Annotation Investigations of skeletal remains from key archaeological sites reveal new data and offer insights on prehistoric life and health in theSoutheast. The shift from foraging to farming had important health consequences for prehistoric peoples, but variations in health existedwithin communities that had made this transition. This new collection draws on the rich bioarchaeological record of the Southeastern United Statesto explore variability in health and behavior within the age of agriculture. It offers new perspectives on human adaptation to various geographic andcultural landscapes across the entire Southeast, from Texas to Virginia, and presents new data from both classic and little-known sites. The contributors question the reliance on simple cause-and-effect relationships in human health and behavior by addressing such key bioarchaeological issues as disease history and epidemiology, dietary composition and sufficiency, workload stress, patterns of violence, mortuary practices, and biological consequences of European contact. They also advance our understanding of agriculture by showing that uses of maize were more varied than has been previously supposed. Representing some of the best work being done today by physical anthropologists, this volume provides new insights into human adaptation for both archaeologists and osteologists. It attests to the heterogeneous character of Southeastern societies during the late prehistoric and early historic periods while effectively detailing the many factors that have shaped biocultural evolution. Contributors include: Patricia S. Bridges, Elizabeth Monaham Driscoll, Debra L. Gold, Dale L. Hutchinson, Keith P. Jacobi, Patricia M. Lambert, Clark Spencer Larsen, Lynette Norr, Mary Lucas Powell, Marianne Reeves, Lisa Sattenspiel, Margaret J. Schoeninger, Mark R. Schurr, Leslie E. Sering, David S. Weaver, and Matthew A. Williamson.